ANALYSIS OF LOW WALL AND HIGH WALL SLOPE STABILITY OF PT XYZ COAL MINE - Putra Delfad, Detri
PT XYZ is one of the coal mining companies operating in South Kalimantan Province. PT XYZ intends to evaluate the stability of high wall and low wall slopes in the Life of Mine (LOM) design. This study aims to determine the stability of the LOM design slope. The classification of whether the slope is safe or not is based on the Minister of Energy and Mineral Resources Decree No. 1827K/30/MEM/2018 by calculating the Safety Factor (SF) in static and dynamic conditions and calculating the Probability of Failure (PoF). Based on the analysis results, the high wall and low wall slope is in a stable condition with static FK ? 1.3, dynamic FK ? 1.5 and PK ? 5%. The results of the analysis showed that the dynamic factor of safety, static factor of safety, and probability of failure of all the section is in compliance to the Minister of Energy and Mineral Resources Decree No. 1827K/30/MEM/2018.